Is there a role for fractional flow reserve in coronary artery bypass graft (CABG) planning? - Ahmadi, Amir; Stanger, Dylan; Puskas, John; Taggart, David; Chandrashekhar, Y.; Narula, Jagat (Annals of Cardiothoracic Surgery, 2018)
The concept of significant lesions has substantially evolved over the last decade. With growing evidence for use of fractional flow reserve (FFR) as a determinant of lesion-specific ischemia and its superiority to angiography-guided revascularization and medical therapy, the field of percutaneous revascularization has shifted to rely exclusively on FFR instead of luminal stenosis alone in guiding revascularization. This transition to physiological assessment has not yet made it to the realm of surgical revascularization. FFR-guided therapy has been shown to be superior to angiography-guided therapy mainly by safe deferral of about 1/3rd of lesions, leading to less periprocedural events and better outcomes. Is it possible that utilization of FFR-guided CABG would lead to less complicated procedures, shorter operating times, more frequent off pump CABG procedures and more hybrid procedures? Can FFR-guided CABG improve the cardiovascular outcomes as compared to current standard of practice? In the following paragraphs we review the concept of FFR, the evidence behind FFR-guided therapy, the emerging data regarding use FFR-guided CABG and discuss where the revascularization field is headed.